Model Transportasi dan Terapannya dalam Optimalisasi Biaya Distribusi Beras Miskin di Kota Makassar oleh Perum Bulog Sub Divre Makassar Tahun 2016 - Rahmat Syam; Sukarna; Muh Nahdi Alim Asyhari (Jurusan Matematika FMIPA UNM, 2019)
This study discusses the transportation model and its application on the stock of Rice Poor (Raskin) in Makassar City by Perum Bulog Sub Divre Makassar. Data is processed by Transport Model. Based on the model is generated a balance model, and export table Raskin distribution,. By method. (LC) and Vogel's Approximation Method (VAM) obtained a feasible initial solution. The method using the stepping stone method (Stepping Stone method). It is then simulated using the Pom for Windows application. The results of this study indicate with the application of Transportation Model. In the year. Year 2016 amounted to 1.7% of the calculation of Perum Bulog Sub Divre Makassar.